Needs Analysis for the Development of a Mobile Application Design to Strengthen Religious Moderation through Digital Literacy in West Java - Aang Mahyani; Mahmud, Mahmud; Supiana, Supiana; Mulyana, Mulyana; Opik Abdurrahman Taufik (CV. AFDIFAL MAJU BERKAH, 2024)
This research is motivated by the rapid development and advancement of technology, information, and communication, which have had a significant impact on various aspects of life, including education. Strengthening religious moderation through digital literacy captures the potential of technological developments that are more interactive and structured in relation to religious moderation. This approach is expected to allow users to more easily access religious moderation assessment results and measure students' moderate attitudes. The objective of this study is to analyze the needs for developing a mobile application design aimed at strengthening religious moderation through digital literacy in West Java. The research locations include MAN 5 Bogor Regency, MAN 4 Sukabumi Regency, MAN 1 Sumedang Regency, and MAN 1 Bekasi City. This study serves as the initial stage in the plan to develop a mobile application design for strengthening religious moderation through digital literacy in West Java. The research design employs a naturalistic qualitative approach. The sampling technique used in this research is purposive sampling. The data collection techniques include interviews, observations, and documentation. Data analysis is conducted using data reduction, data presentation, and verification techniques. The needs analysis results indicate that the most essential features for this application include the Digital Literacy Module, Interactive and Practical Materials, Discussion Forum, Online Counseling, and Religious Moderation Assessment. These features are designed to assist users, particularly madrasah students, in understanding the concept of religious moderation through engaging, interactive, and easy-to-understand content. Additionally, the credibility of the content and the security of user data are also key priorities in the development of this application. By addressing these needs, the application will serve as an effective tool for disseminating the values of religious moderation, enhancing digital literacy among the younger generation, and preventing the spread of radical and extremist ideologies. This application is expected to educate and shape a generation that is moderate, inclusive, and respectful of religious diversity in society.